Pemberdayaan Petani Tanaman Tomat di Kelurahan Lowu-Lowu Kecamatan Lea-Lea Kota Baubau - Muhammad Harmadin; Awaluddin Hamzah; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2021)
This study aimed to: (1) determine and analyzed the empowerment of tomato plant farmers in the Lowu-Lowu Village, Lea-Lea District, Baubau City. (2) Knowed and analyzed tomato plant cultivation in Lowu-Lowu Village, Lea-Lea District, Baubau City. (3) Knowed the relationship between the empowerment of tomato cultivation in the empowerment of tomato farmers in the Lowu-Lowu Village, Lea-Lea District, Baubau City. This research was conducted in the Lowu-Lowu Village, Lea-Lea District, Baubau City which was carried out from December 2020 to January 2021 with a population of 25 respondents while the determination of the sample for the Lowu-Lowu sub-district using the census method, namely all members of the population were used as research subjects. Data analysis used quantitative analysis. The results showed that (1) Empowerment of tomato plant farmers in Lowu-Lowu Village, Lea-Lea District, Baubau City has been carried out well, where awareness and desire, level of ability to increase capacity, level of ability to face obstacles and level of ability to cooperate in farmer empowerment activities already well. (2) Cultivation of tomato plants by farmers in Lowu-Lowu Village, Lea-Lea District, Baubau City has been carried out well, which was viewed from soil cultivation, seed sowing, planting, watering, initial fertilization, pruning, weeding, fertilization after control pests and diseases in tomato cultivation activities have been done well by farmers in this research area. (3) there was a fairly close relationship between farmer empowerment activities and tomato cultivation. Where the better the empowerment of farmers, the better the cultivation of tomato plants.